The impact of nominal negative interest rates on the economy: Literature review - Jakub Kubiczek (Journal of Banking and Financial Economics (JBFE), 2022)
Until recently, negative nominal interest rates of the central bank were in the sphere of theoretical considerations. In 2009, the Swedish Central Bank was the first to implement a negative interest rate policy (NIRP). Since then, the NIRP has been implemented by the National Bank of Denmark, the European Central Bank, the Swiss National Bank and the National Bank of Japan. Unfortunately, due to the large number of simultaneous factors affecting the economy, it is extremely difficult to determine the long-term effects of NIRP implementation. Furthermore, the magnitude of the impact and the global extent of the coronavirus pandemic would have a significant impact on the dilatation, so the focus was on pre-pandemic issues. This paper is a literature review and it aims to synthetize information about the impact of negative interest rates on the market - in financial and real spheres. In this paper, both the results of scientific research and the opinions of experts were used, then the impact of negative nominal interest rates on the financial and real sectors was assessed. The results show that most authors highlight an adverse impact of negative interest rates on the stability of the banking sector regardless of the country. The greatest fear of the NIRP implementation by central banks is that the potential behavior of economic entities cannot be predicted with certainty, especially when it comes to cash deposit withdrawals from banks.
Keywords: E43; E44; E52; E58; 330; interest rates; nominal negative interest rates; NIRP; monetary policy